Evidence of association between aerosol properties and in-vitro cellular oxidative response to PM1, oxidative potential of PM2.5, a biomarker of RNA oxidation, and its dependency on combustion sources. (15th September 2019) - Costabile, F.; Gualtieri, M.; Canepari, S.; Tranfo, G.; Consales, C.; Grollino, M.G.; Paci, E.; Petralia, E.; Pigini, D.; Simonetti, G.
Abstract: The causal link between ambient PM2.5 and adverse health effects is still not clear enough, nor it is clear what factors (physical and/or chemical) contribute to PM2.5 toxicity and by what mechanism(s). With a view on this, we launched the CARE experiment, during which we performed a comprehensive characterisation of the physicochemical properties of fine and ultrafine particles under exposure levels dominated by the urban combustion aerosol, and their toxicological assessment through in-vitro tests (lung epithelia cells cultured at the ALI) directly under ambient conditions, oxidative potential (determined through 2′, 7′-dichlorouorescin, OP DCFH ), and human biomonitoring. We already reported about aerosol characterisation, and in-vitro model results during CARE. Building upon these, in this work we assess the combustion aerosol oxidative response through the analysis of consistency between the three independent aerosol oxidative responses obtained, and the exploration of any causality link with the combustion aerosol. This is the first time to our knowledge that combustion related PM2.5 physicochemical properties and its OP DCFH are compared to the cellular-oxidative response (C-OR) obtained through the PM in-vitro test carried out (for the first time) directly under atmospheric ambient conditions, and to certain biomarkers of oxidative damage to DNA/RNA (8-oxo-7, 8-dihydroguanine, 8-oxo-7, 8-dihydro-2′-deoxyguanosine and 8-oxo-7, 8 - dihydroguanosine). Our results provide a first evidence of a combustion-dependent association between the in vitro C-OR, the PM2.5 OP DCFH, and the urinary excretion of the 8-Oxo-7, 8-dihydroguanosine. Yet this is not a substantial basis for drawing any cause-effect relationship. However, our findings support previous literature suggesting a link between combustion and oxidative response of PM2.5 . Moreover, we add a consistency across completely independent oxidative response measurements with a possible dependence on the combustion traffic-related aerosol. This is a piece of information that may have important implications in the understanding of how combustion sources contribute to oxidative response related diseases. Graphical abstract: Image 1